Peran Limfosit T Helper-1 (TH1) dan T Helper-2 (TH2) pada Patogenesis Artritis Lepra - Suyanto Hadi; Sunarto Sunarto; Hardyanto S; Triyuliati Triyuliati; Susanto J; F.X. Hartono (MEDIA MEDIKA INDONESIANA, 2008)
ABSTRACTThe role of lymphocyte T Helper-1 (TH1) and T Helper-2 (TH2) in the pathogenesis of leprosy arthritisBackground: The autoreactive of TH CD4+ cells is the thought to play an important role in arthritis leprosy pathogenesis. However, wheter of TH1 or TH2 predominant has never been studied.Methods: Various Ag M. leprae (Ag 35 kDa, 10 kDa, 45 kDa, 85 kDa, and MLSA 2 ug/ml) were stimulated to the peripheral blood (10cc) lymphocyte culture (PBMC) using 96 weels microplate and RPMI 1640 media of 22 leprosy arthritis cases, control-1 (n=12) (leprosy without arthritis) and control 2 (n=12) (healthy contact). The activity difference between TH1 and TH2 CD4+ lymphocyte was analysed using the difference delta levels of IFN-γ and IL-4 (ELISA) of the three group studies. Statistical analysis used wereANOVA, Kruskal Wallis or Mann Whitney, and Chi-square.Results: IFN-γ delta levels was significantly higher in the lymphocytes cultures in LA group (the median 132.234 pg/ml, 60.347 g/ml, 14.093 pg/ml, 16.619 pg/ml and 138.394 pg/ml) compared with IL-4 value level (median 0.317 pg/ml, 0.017 pg/ml, -0.206 pg/ml, -0.200 pg/ml and 0.492 pg/ml) after being stimulated with 35 kDa, 10 kDa MMP-1, 45 kDa LAM, 85 kDa and MLSA of 2 ug/ml dose consecutively (all p<0.001). The IFN-γ delta value in LA group also showed the significantly higher level in response toall M. leprae Ag compared to all control-groups, with all p value < 0.05.Conclusion: TH1 CD4+ lymphocyte activity is more dominant compared than TH2 CD4+ lymphocyte activity in leprosy arthritis group patients.Key Words: Leprosy arthritis, IFN-γ, IL-4, TH1 CD4+ and TH2 CD4+ lymphocyte, and M. leprae Ag ABSTRAKLatar belakang: TH CD4+ autoreactive diduga kuat pada patogenesis artritis lepra. Apakah autoimunitas akibat dominansi aktivasi limfosit TH1 atau TH2 pada penderita lepra belum pernah diteliti.Metode: Berbagai Ag M.leprae (35 kDa, 10 kDa, 45 kDa LAM, 85 kDa, dan MLSA dosis 2 ug/ml) distimulasikan pada kultur limfosit darah perifer (10 cc darah vena), menggunakan media RPMI 1640 dari 22 kasus artritis lepra, 12 kontrol-1 (lepra tanpa artritis), dan 12 kontrol-2 (tetangga sehat kontak positif). Nilai delta kadar IFN-γ dan IL-4 (ELISA) diukur untuk mengetahui peran aktivitas limfosit TH1 dan TH2. Statistik yang dipergunakan uji ANOVA, uji Kruskal-Wallis atau Mann Whitney, dan metode Chi-square.Hasil: Nilai delta IFN-γ kultur limfosit kasus artritis lepra (median 132,234 pg/ml, 60,347 pg/ml, 14,093 pg/ml, 16,619 pg/ml dan 138,394 pg/ml) kelompok LA lebih tinggi bermakna dibandingkan nilai delta IL-4 (median 0,317 pg/ml, 0,017 pg/ml, -0,206 pg/ml, - 0,200 pg/ml dan 0,492 pg/ml) pasca stimulasi dengan Ag M. leprae 35 kDa, 10 kDa MMP-1, 45 kDa LAM, 85 kDa dan MLSA dosis 2 ug/ml, (p<0,001). Nilai delta IFN-γ kelompok kasus juga lebih tinggi dibandingkan kedua kelompok kontrol (p< 0,05).Simpulan: Aktivitas limfosit TH1 CD4+ lebih dominan dibandingkan TH2CD4+ pada kelompok penderita artritis lepra.